The answer is E(CA)=EA*EB. This is why: You have C=A*B. Therefore, E(CA)=E((A**2)*B))=E(A*B)=EA*EB. The second to last equality holds because A**2=A, and the last one is correct because A and B are independent.
Vadim [EMAIL PROTECTED] (John Smith) wrote: > If I have 3 variables defined as follows: > > A, B as independent, uncorrelated values of 0 or 1 > C defined as the logical AND of A&B, such that C=1 if and only if both > A & B =1, and 0 otherwise. > > Example > > A=1, B=0 then C=0 > A=0, B=1 then C=0 > A=0, B=1 then C=0 > A=1, B=1 then C=1 > > My question is, what is the covariance (or how does one begin to > calculate it) between A and C ? ================================================================= Instructions for joining and leaving this list, remarks about the problem of INAPPROPRIATE MESSAGES, and archives are available at http://jse.stat.ncsu.edu/ =================================================================